(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Newcastle disease virus genotype VII (NDV-GVII), an extremely infectious pathogen, has been causing severe economic consequences for the chicken industry. The current study aimed to isolate and characterize NDV-GVII from commercial chickens in Bangladesh during a recent outbreak. Materials and Methods: From clinically suspected chickens from 70 commercial poultry farms, a total of 420 samples (trachea, lungs, and brain tissue) were collected. The samples were cultivated in 9–10 day-old seronegative embryonated chicken eggs (ECEs) after evaluating them using the rapid Newcastle disease virus (NDV) antigen detection kit. The hemagglutination (HA) inhibition test, agar gel immune diffusion (AGID) test, molecular detection by reverse transcription-polymerase chain reaction (RT-PCR), and phylogenetic studies using gene sequences of fusion (F) protein. The HA pattern of isolated NDV was determined using different avian and mammalian red blood cells (RBCs). The pathogenicity of the isolated virus was evaluated using mean death time (MDT), intravenous pathogenicity index (IVPI), and intracerebral pathogenicity index (ICPI). Results: The study found 87 NDV samples positive using the rapid NDV Ag detection kit and then 60 positives for virus isolation in ECEs. All 60 isolates were positive for NDV by HI, AGID, and RT-PCR. Phylogenetic tree analysis indicated that recent NDV isolates belong to genotype VII and exhibit a similarity of 99.7%–98.5% with isolates from Bangladesh, Iran, and India. The new isolates, identified as velogenic strains of NDV, possess an F protein cleavage site with 112-R-T-K-R-F-117 amino acid motifs. The isolated NDV showed diversified HA activity while using RBCs from birds and mammals. The results of ICPI, IVPI, and MDT indicated that the recent NDV isolates were very virulent. Conclusion: This study concluded that NDV-GVII is prevalent in commercial poultry farms in Bangladesh. Adv. Vet. Anim. Res., 11(2): 408-417, June 2024 http://doi.org/10.5455/javar.2024.k790